Experimental study on immiscible and miscible dynamic characteristics of CO2 and crude oil in visual slim tube - Xing Zhang; Dongchen Ma; Ruiming Zhao; Xiaoyu Zhang; Jiajia Feng; Meng Feng (CT&F Ciencia, Tecnología & Futuro)
CO2 flooding for oil recovery is a dynamic process that requires further investigation of oil-gas interface change characteristics, interfacial mass transfer processes, and oil-gas composition variation during both immiscible and miscible displacement. Understanding these factors is crucial for better comprehending their impact on CO2-enhanced oil recovery (EOR). This research used a jointly developed CO2 miscible visual flooding experimental apparatus to study the horizontal dynamic characteristics of CO2 and crude oil under different pressures and flow rates in visual slim tube. At 10 MPa, the stratification results of CO2 and crude oil indicate that the experiment is immiscible flooding. The contact angle (7.9°) between the two phases of CO2 and crude oil at the flow rate of 15 cm/min is larger than that (5.2°) at 1.5 cm/min, and the grey scale of CO2 increases at 100 cm/min. The quantity, individual content, and shape of the light and medium hydrocarbon components condensed on the inner wall of the tube vary with different flow rates. At 15 MPa, the appearance of the CO2 and crude oil transition interval proves that the experiment is miscible flooding. At different flow rates, the inclination angle and distribution of black stripes vary. The whole transition interval is divided into 6 intervals, and the transition interval lengthens with increasing fluid velocity. The experiments visually demonstrate the occurrence of the miscible phase, and identify experimental pressure and fluid flow rate as key factors influencing the miscibility of CO2 and crude oil.